Mimicry boosts social bias: unrealistic optimism in a health prevention case - Wojciech Kulesza; Dariusz Dolinski; Paweł Muniak; Aidana Rizulla (Social Influence, 2023)
Unrealistic optimism bias appears when a person perceives oneself – in comparison to peers – as less at risk from threats. This bias has been widely reported and the consequences are clear: it puts one’s health in danger. The existing body of literature proposes egocentrism as a mechanism leading to a reduction in this bias. The present paper tests a novel mechanism orienting a person toward others – thus linked with egocentrism – i.e., mimicry. Results showed directly opposing effects: mimicry induced a stronger tendency to perceive oneself as less threatened. This result is not only surprising but especially alarming since mimicry may be used in patient-doctor dialogue which may backfire, leading to resistance to medical recommendations provided by the doctor.